The Relationship between Carrying Activity and Low Back Pain:A Critical Review of Biomechanics Studies - Hanif Farhan; White, M. R; Warner, P. J; Adam; J. E (Penerbit UKM, 2015)
The aim of this review was to systematically explore the underlying musculoskeletal biomechanical mechanisms of carrying and to describe its potential relationship with low back pain. This literature review was carried out using AMED, CINAHL, Compendex and MEDLINE electronic databases. Articles published from 2004 to 2012 were selected for consideration. Articles were considered if at least one measurement of kinetics, kinematics or other related musculoskeletal parameters related to biomechanics were included within the study. After combining the main keywords, 677 papers were identified.However, only 10 studies met all the inclusion criteria. Age, body mass index, gender and level of physical activity were identified as the factors that may influence the biomechanics of carrying activity. Carrying a loaded backpack was reported leading to posterior pelvic tilt, reduced lumbar lordosis, but increased cervical lordosis, thoracic kyphosis and trunk forward lean. Furthermore, while carrying bilaterally, lumbo pelvic coordination was also reported to be more in phase, as well as reduced coordination variability in transverse plane. Future studies investigating the biomechanics of a standardized carrying activity for clinical test are recommended.